University students' succession intention: GUESSS Colombia study evidence [Intención de sucesión en estudiantes universitarios: Evidencia del estudio GUESSS] (2018)
Despite critical research on career choice intentions, we lack understanding of the antecedents to career choice intentions of successors, especially in emerging economy contexts. Building on the theory of planned behavior and with data obtained from GUESSS project, the article aims to analyze university students' career choice intentions within a family business context. Our findings suggest that students with family business background are pessimistic about being successor, but optimistic about pursuing an entrepreneurial career. The paper contributes to the entrepreneurship literature by adding up insights from emerging countries to the debate. © 2018.A pesar de la creciente investigación sobre intención de elección de carrera, todavía hace falta una mayor comprensión de los antecedentes de intención de ser sucesor, especialmente en contextos de economías emergentes. Apoyados en la teoría del comportamiento planeado y con datos del proyecto GUESSS, el artículo tiene como objetivo analizar las intenciones de elección de carrera de estudiantes universitarios en el contexto de empresa familiar. Nuestros hallazgos sugieren que estos estudiantes son pesimistas acerca de ser sucesores, pero optimistas respecto a seguir una carrera empresarial. El documento contribuye a la literatura sobre emprendimiento al tener evidencia de países emergentes. © 2018.